1990
DOI: 10.1007/bf01536791
|View full text |Cite
|
Sign up to set email alerts
|

Bile acids reversible effects on small intestinal permeability

Abstract: To define the action of deconjugated bile acids on the small intestinal permeability in an in vitro system, we investigated the effects of chenodeoxycholic acid and ursodeoxycholic acid on the rate of transmural flux of lactulose in jejunal and ileal mucosa of rabbits, stripped of their muscle layers and mounted in Ussing chambers. In a series of experiments, tissue samples from small intestinal segments either exposed to bile acids or not also were examined by scanning and transmission electron microscopy to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 25 publications
2
26
0
Order By: Relevance
“…However, the recovery times are highly dependent upon the type of model used in the study. For example, when the rabbit jejunum was treated with 0.5 mM chenodeoxycholate for 25 min in an in vitro system, mucosal permeability to lactulose returned to the normal value after 40 min (52). Similarly, when the guinea pig ileum was exposed to 0.06% Triton-X 100 (0.75 mM) for 5 min in an in vitro model, it took one hour for the tissue to seal the defect, when observed under a light microscope (53).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…However, the recovery times are highly dependent upon the type of model used in the study. For example, when the rabbit jejunum was treated with 0.5 mM chenodeoxycholate for 25 min in an in vitro system, mucosal permeability to lactulose returned to the normal value after 40 min (52). Similarly, when the guinea pig ileum was exposed to 0.06% Triton-X 100 (0.75 mM) for 5 min in an in vitro model, it took one hour for the tissue to seal the defect, when observed under a light microscope (53).…”
Section: Discussionmentioning
confidence: 84%
“…Examples of these materials include spices such as pepper (23,24) and garlic (25,26), hydrolytic food products and fatty meals (27,28), and alcoholic beverages (29,30). Drugs like NSAIDs (31,32), common laxatives (33)(34)(35) which are used commonly on a recurring basis and chenodeoxycholic acid (36)(37)(38) which has been used therapeutically since the early 1970's for the dissolution of gallstones for up to 2 years, have been shown to cause reversible damage in the gastrointestinal mucosa (39).…”
Section: Introductionmentioning
confidence: 99%
“…Our patients were not taking ASA, NSAIDs, or alcohol, all known to affect permeability, at the time the test was performed [28,29]. Bile acids have been shown to reversibly increase jejunal and ileal permeability in rabbits, however, this has not been studied in humans [30]. If UDCA had a major effect on human intestinal permeability, a greater proportion of the PBC cohort would likely have had abnormal results given that they were all on therapy.…”
Section: Discussionmentioning
confidence: 98%
“…Since high counts of aerobic and anaerobic bacteria have been found in the jejunal secretion of infants with persistent diarrhea, it has been suggested that bacterial proliferation could be responsible for the perpetuation of diarrhea and nutrient malabsorption (23). In fact, bacterial overgrowth in the small bowel lumen may be responsible for several functional and morphological abnormalities such as deconjugation and 7 a dehydroxylation of primary bile salts (24), sodium and water secretion (25), glucose malabsorption (26) and rupture of the intestinal permeability barrier favoring the penetration of intact macromolecules (27), and thus potentially leading to food allergy. Colitis was observed in 10 patients but an enteroinvasive microorganism was isolated from only 2 of them, and therefore food allergy might account for the remaining cases of colitis observed in our series.…”
Section: Discussionmentioning
confidence: 99%